Pengaruh kepemilikan institusional, dewan komisaris independen dan komite audit terhadap tax avoidance - Irma Nurwulan; R Ait Novatiani (LPMP Imperium, 2026)
This study aims to examine the effect of institusional ownership, an independent board of commissioners, and an aduit committee on tax avoidance. The population used was 228 manufacturing companies listed on the Indonesia Stock exchange (IDX). Purposive sampling was used as the sampling technique, resulting in a total sample of 34 manufacturing companies. Panel data regression analysis was used in this study using Eviews 12. The result showed that institusional ownership an independent board of commissioners has an effect on tax avoidance and audit committee has no effect on tax avoidance. This study found that the interests of the largest institutional shareholders drive tax supervision, and the role of independent boards of commissioners is more likely to pressure companies to comply with tax regulations than the internal control mechanisms of the audit committee. Public interest statements The results encourage regulators to enhance the independence of audit committees so that they are not merely a formality. Companies are better off making their financial statements more transparent so that taxes can be paid in accordance with legal regulations